2012
DOI: 10.1890/es12-00031r
|View full text |Cite
|
Sign up to set email alerts
|

Climate fluctuations and differential survival of bridled and non‐bridled Common GuillemotsUria aalge

Abstract: Abstract. Climate fluctuations and its effects on ecological processes are evident in most areas worldwide but whether such climatic effects are induced phenotypic plasticity or whether animals adapt to the new environment through micro-evolutionary processes is poorly known. In this study we have analyzed long-term data (22 years) on the relationship between climatic fluctuations and the adult survival of two distinct genetic morphs of the Common Guillemot (Uria aalge) breeding in a colony in the southern Bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Similar temporal changes in morph ratios according to environmental factors were observed in other polymorphic species (e.g. in the Tawny owl Strix aluco Karell, Ahola, Karstinen, Valkama, & Brommer, ; or in the Common murre Uria aalge Reiertsen, Erikstad, Barrett, Sandvik, & Yoccoz, ). These results suggest that, at least in some species, colour polymorphism embodies the existence of different evolutionary responses to different environmental conditions within populations.…”
Section: Discussionsupporting
confidence: 70%
“…Similar temporal changes in morph ratios according to environmental factors were observed in other polymorphic species (e.g. in the Tawny owl Strix aluco Karell, Ahola, Karstinen, Valkama, & Brommer, ; or in the Common murre Uria aalge Reiertsen, Erikstad, Barrett, Sandvik, & Yoccoz, ). These results suggest that, at least in some species, colour polymorphism embodies the existence of different evolutionary responses to different environmental conditions within populations.…”
Section: Discussionsupporting
confidence: 70%
“…The un-lagged effect is related to the adult return rate (resighting rate) to the colony each year. As the adult survival rate at Hornøya is high and near constant [40] , the resighting rate probably reflects the part of the population that defers breeding in any year such that the presence of young cod near Hornøya might be an important determinant of the adults’ decision to breed or not to breed.…”
Section: Discussionmentioning
confidence: 99%
“…Even for the same species in different studies, results are not always similar (see Table 1), suggesting differences among populations (Tavecchia et al, 2008) or raising doubts about the suitability of selected climate indexes, the temporal window analyzed or the power of each data set to detect associations between climate and the seabird parameter of interest, especially when these associations are not statistically significant (Jenouvrier, 2013). For instance, some studies found that the influence of increased SST on adult survival was positive or negative depending on the study colony or the genetic morph (Harris et al, 2005;Reiertsen et al, 2012), and these are good examples of how little we still know about the mechanisms linking climate and vital rates (Forero et al, 2001). Finally, non-linear relationships between demographic parameters and climate indices can also result in differences between studies on the same species when different temporal windows are considered.…”
Section: Pitfalls and Gaps Of The Climate-seabird Researchmentioning
confidence: 99%